Integration-negative mutants of bacteriophage lambda - Gottesman, Max E.; Yarmolinsky, Michael B. (Journal of molecular biology, 1968)
Mutants of bacteriophage lambda unable to form stable lysogens have been obtained by a simple screening procedure. These mutants, designated int, form turbid plaques. The procedure used for their isolation also allows the titration and selection of rare lysogens in a predominantly non-lysogenic population. The recombinational behavior of int mutants in wild-type and recombination-deficient ( rec) bacteria suggests that the int + gene determines a site-specific function involved in normal prophage integration and detachment. The Int function can be provided in trans by an int + phage. The expression of the int + gene is subject to repression by the phage immunity substance. Single int lysogens give a low yield of active phage upon induction, whereas double lysogens, when tandem, give nearly normal phage yields. Both single and double int lysogens give large yields of transducing particles. Recombination between vegetative int phages and productive induction of int lysogens, both of which occur in recombination-deficient bacteria, may be attributed to a separate function (Red) operative in phage-infected or induced cells. The Red function is not available for use in integration of a superinfecting phage, a function which the product of the bacterial rec + gene can accomplish.